Pencegahan Penyakit DBD Melalui Larvitrap Sederhana dari Pemanfaatan Sampah Botol Plastik - Dyah Hapsari Muliajati; Haifa Fitria Damayanti Fitria; Yuni Rahmawati Rahmawati; Adiska Rizqi Ramadina Rizqi; Irsan Cahya Brianto Cahya; Sri Muryani Muryani (JPS : Jurnal Pengabdian Serulingmas, 2023)
The last DHF case in Wadas Village, Tridadi, Sleman, Special Region of Yogyakarta occurred in 2021, to prevent cases in subsequent years, it is necessary to do various programs such as the making of Larvitrap. Counseling and practice of making Larvitrap aims to increase the knowledge and ability of the community in eradicating the Aedes aegypty mosquito as the vector that causes DHF. This activity was carried out using several methods, namely counseling, question and answer, and the practice of making Larvitrap together. Before making Larvitrap, it was preceded by counseling on the meaning of DHF, symptoms of DHF, prevention of DHF with environmental sanitation, and methods for making simple Larvitrap appropriate technology. The enthusiasm of participants is reflected in their efforts when carrying out the making of Larvitrap and many questions that arise such as the method or working principle of the Larvitrap that causes mosquitoes to get trapped in it. Through the making of Larvitrap, it is hoped that the community in Wadas Village can participate in supporting the Tanggap Bocah (TABO) and become a form of plastic bottle waste processing activity into simple appropriate technology.